2008 3rd IEEE Symposium on New Frontiers in Dynamic Spectrum Access Networks 2008
DOI: 10.1109/dyspan.2008.82
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Spectral Resources in Cognitive Radios Using Reinforcement Learning

Abstract: Abstract-Available spectrum for wireless communications is a limited resource which gains importance with the increasing demand for mobile communication services with high data rates. Measurements show, that assigned frequency bands (FBs) are not used efficiently. One approach for increasing the efficiency in spectrum use is the concept of overlay systems, which can be seen as an enabling technology for cognitive radio and dynamic spectrum access by providing frequency agility. In this paper, we propose an app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 8 publications
0
38
0
Order By: Relevance
“…Control signaling to inform users about the chunks that are used in the cell is assumed. Notice also that P m does not depend of the chunk in (5) and (6). This is because transmitted power per chunk is constant and average path loss and shadowing is assumed to be non-frequency dependent into the service bandwidth.…”
Section: Short-term Scheduler (Sts)mentioning
confidence: 92%
See 1 more Smart Citation
“…Control signaling to inform users about the chunks that are used in the cell is assumed. Notice also that P m does not depend of the chunk in (5) and (6). This is because transmitted power per chunk is constant and average path loss and shadowing is assumed to be non-frequency dependent into the service bandwidth.…”
Section: Short-term Scheduler (Sts)mentioning
confidence: 92%
“…RL shows inherent cognitive capabilities since it consists in learning the suitable set of actions to choose in order to maximize a numerical reward given that there is a continuous interaction with an environment. Hence, RL has been successfully applied to spectrum sensing [6] or spectrum sharing [7] procedures in Cognitive Radio (CR). Also, in our previous work, we showed that RL can be used to implement centralized dynamic spectrum assignment (DSA) strategies for primary cellular networks [8].…”
Section: Introductionmentioning
confidence: 99%
“…In [5], RL is applied in DCS among the Base Stations (BS)s in order to enable each BS to cover a minimum percentage of service area with the highest SINR so as to reduce call blocking and dropping probability. In [6], RL is applied to identify channels with the most available white spaces at the BS in centralized networks. In [7], RL is applied in spectrum assignment strategy in OFDMA networks in order to improve the PU's performance metrics including spectral efficiency, users' Quality of Service (QoS) satisfaction, and the amount of licensed spectrum to be released to SUs.…”
Section: Introductionmentioning
confidence: 99%
“…In [7], RL is applied in DCS among the base stations in order to enable each of them to cover a minimum percentage of service area with the highest SINR so as to reduce call blocking and dropping probability. In [8], RL is applied to identify channels with the most available white spaces at the base station in centralized networks. In [9], RL is applied in spectrum assignment strategy in OFDMA networks in order to improve the PU's performance metrics including spectral efficiency, users' quality of service satisfaction, and the amount of licensed spectrum to be released to SUs.…”
Section: Introductionmentioning
confidence: 99%